Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1186/s13018-021-02706-w
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of intercondylar notch size and shape in patients with cyclops syndrome after anterior cruciate ligament reconstruction

Abstract: Background Cyclops lesion is the second most common cause of extension loss after anterior cruciate ligament reconstruction. This study focused on the correlation between the anatomy of the intercondylar notch and the incidence of cyclops lesion. To determine whether the size and shape of the intercondylar notch are related to cyclops lesion formation following anterior cruciate ligament reconstruction according to magnetic resonance imaging (MRI) findings. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…Moreover, it was observed that a narrow notch was a more important factor for increased signal intensity of the entire intra-articular graft, especially at the mid-substance of the graft, which was in accordance with a previous report [39]. Narrow intercondylar notches are associated with greater impingement, which can lead to graft degeneration, and is considered a predictive factor for ACL injury [10,22,37,39]. In the present study, we also analyzed the association of the narrow intercondylar notch with impingement in the reconstructed graft.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, it was observed that a narrow notch was a more important factor for increased signal intensity of the entire intra-articular graft, especially at the mid-substance of the graft, which was in accordance with a previous report [39]. Narrow intercondylar notches are associated with greater impingement, which can lead to graft degeneration, and is considered a predictive factor for ACL injury [10,22,37,39]. In the present study, we also analyzed the association of the narrow intercondylar notch with impingement in the reconstructed graft.…”
Section: Discussionsupporting
confidence: 91%
“…They found that the percentage of the total femoral tunnel size to CSA was significantly higher in the patients with cyclops lesions than in those patients without cyclops lesions. A recent study [10] also indicated that the shape of the intercondylar notch as well as the size was related to cyclops lesion formation after ACL‐R. As the evaluation for the femoral notch using NWI does not take into account the shape of the intercondylar notch or the ACL graft volume in relation to the notch size [18, 33], NWI may not be associated with the presence of cyclops lesions and syndrome in this study.…”
Section: Discussionmentioning
confidence: 65%
“…Several authors have reported that femoral intercondylar size and shape were related to the risk of cyclops lesion after ACLR. 14,15,41 However, to the best of our knowledge, no studies have reported the association between morphological factors of tibial spines and loss of knee ROM after ACLR. Iriuchishima et al radiographically evaluated whether or not tibial spine heights, TSW, and NWI were associated with the occurrence of ACL injury, 16 suggesting that a larger TSW may contribute to knee stabilization, which may decrease the risk of ACL injury.…”
Section: Discussionmentioning
confidence: 99%